Recreational drug use: an emerging concern among venue-based male sex workers in China - Liu, Shusen (2012)
A 2009 survey of 418 venue-based male commercial sex workers (male CSWs) in Shenzhen, China revealed that 19.9% used recreational drugs. Consistent condom use by drug users was lower than by non-users. HIV, syphilis, and herpes simplex virus 2 (HSV-2) prevalence, however, were higher among drug users. Prevention programs need to address drug use among male CSWs in China.